2019
DOI: 10.1016/j.gca.2019.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Frictional melt homogenisation during fault slip: Geochemical, textural and rheological fingerprints

Abstract: Volcanic environments often represent structurally active settings where strain localisation can promote faulting, frictional deformation, and subsequent melting along fault planes. Such frictional melting is thermodynamically a disequilibrium process initiated by selective melting of individual mineral phases and softening of volcanic glass at its glass transition as a response to rapid frictional heating. The formation of a thin melt layer on a fault plane surface can drastically accelerate or terminate slip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 95 publications
0
14
0
Order By: Relevance
“…In addition to the measured temperature of the frictional melt during the experiment LHVR1097, we also estimated the possible viscosity and temperature of the friction melt in the four states following the method suggested by Wallace et al (). The non‐Arrhenian Newtonian temperature‐dependence viscosity of the silicate melt can be estimated by the GRD viscosity calculator (available online at https://www.eoas.ubc.ca/~krussell/VISCOSITY/grdViscosity.html) by inputting the melt composition (Table ; Giordano et al, ; Lavallée et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the measured temperature of the frictional melt during the experiment LHVR1097, we also estimated the possible viscosity and temperature of the friction melt in the four states following the method suggested by Wallace et al (). The non‐Arrhenian Newtonian temperature‐dependence viscosity of the silicate melt can be estimated by the GRD viscosity calculator (available online at https://www.eoas.ubc.ca/~krussell/VISCOSITY/grdViscosity.html) by inputting the melt composition (Table ; Giordano et al, ; Lavallée et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Experiments pointed out a more mafic composition of the molten mass at the onset of melting. With the melting process ongoing during shearing, the molten mass becomes felsic, and its composition approaches that of the protolith (De Blasio & Elverhøi, 2008; Wallace et al, 2019). This confirms the importance of studying the variation of viscosity in relation to selective melting.…”
Section: Resultsmentioning
confidence: 99%
“…In tests during which melting occurred, it was observed that the remaining (non‐melted) fragments were predominantly quartz crystals, with minor presence of plagioclase. Although the chemical composition of the molten fraction is different compared to that of the protolith at the onset of melting, it approaches the latter as temperature increases and melting proceeds (Masch et al, 1985; Wallace et al, 2019). Selective or “preferential” melting is the generally accepted process thought to occur in rock sliding, rather than eutectic reactions (Lin & Shimamoto, 1998; Spray, 1992), and it might affect the rheological properties of the molten layer.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, fault slip can generate a substantial amount of frictional heating (Carslaw and Jaeger, 1959). The thermal conductivities and, where relevant, decomposition, breakdown or melting temperatures of each constituent phase of the material also determine the progression of frictional heating during sliding (e.g., Spray, 2010;Wallace et al, 2019a). It is the pairing of comminution with the production and conduction of frictional heat away from the slip interface, determined by the nature of the material, that acts to dissipate the energy of slip events (e.g., Lavallée and Kendrick, 2020 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The frictional behaviour of rocks has been studied extensively using field observations (e.g., Sibson, 1994;Mitchell et al, 2016;Hughes et al, 2020), controlled laboratory experiments (e.g., Byerlee, 1978;Marone, 1998;Scholz, 1998;Hirose and Shimamoto, 2005a;Hirose and Shimamoto, 2005b;Di Toro et al, 2006;Di Toro et al, 2011;Kendrick et al, 2014;Hornby et al, 2015;Wallace et al, 2019a), and modelling (e.g., Nielsen et al, 2008;Weng and Yang, 2018). In an early attempt to reconcile laboratory data, Byerlee (1978) advanced that at low slip velocities and shallow crustal conditions (<200 MPa normal stress), the shear resistance (τ) of rocks during slip is proportional to the normal stress (σ n ), such that:…”
Section: Introductionmentioning
confidence: 99%